Digital Resistance in Indonesia: Critical Discourse and Sentiment Analysis of #KawalPutusanMK on X - Salsabilla, Natasya Ayu; Ma'shumah, Nadia Khumairo; Wijaya, Ayudhia Ratna (Jurnal Gramatika, 2025)
In the contemporary digital era, political participation is increasingly mediated through online spaces, situating social media platforms as pivotal arenas for civic discourse and democratic contestation. This study investigates how Indonesian citizens engage with political issues through the hashtag #KawalPutusanMK on X, in response to decisions by the Constitutional Court. Employing a mixed-methods design, this study integrates computational sentiment analysis with Critical Discourse Analysis (CDA) approach to analyze 3,508 user-generated posts collected between August and September 2024. Focusing on the textual (micro) level, this study examines lexical choices, emotional polarities, and metaphorical constructions that reflect public sentiment and their ideological stance. Findings show a predominance of negatively charged discourse, particularly targeting political elites and institutions. Users frequently employ emotionally loaded vocabulary and metaphors such as portraying democracy as a dying body, politics as theater, political elites as immoral rulers, and resistance as sacred duty serve to further delegitimize institutional authority. These linguistic features signal a broader erosion of public trust and dissatisfaction with institutional legitimacy. Additionally, the discourse constructs collective identity and mobilizes resistance, illustrating how online platforms function as tools for political engagement and symbolic struggle. By uncovering the rhetorical and affective strategies in digital protest, this study contributes to a deeper understanding of how language mediates public criticism and democratic participation in contemporary Indonesia. The findings have implications for media regulation, digital civic literacy, and policy development in a post-authoritarian context. Future research should focus on how digital platform discourse contributes to strengthening democratic resilience and promoting institutional accountability